Using of Babassu and its By-products in Animal Nutrition - Tugay Ayasan (Turkish Journal of Agriculture: Food Science and Technology)
The increasing costs of conventional feedstuffs like corn, soybean meal and fish meal for poultry diets increased the need for cheaper alternatives. Babassu is a tall palm tree species found in Brazil. Babassu meal is high in protein (19.49-20.19%), minerals (1.20% Ca, 0.41% available P) and gross energy, 4553 kcal/kg. The amino acid profile of babassu meal indicates that it is a good source of amino acids especially arginine (2.34%), glycine+serine (1.75%) and phenylalanine+tyrosine (1.32%). In this review, the studies focused on possibilities of using babassu meal in poultry and ruminant rations were discussed.